Studi komparatif: analisis perhitungan biaya produksi berbasis tekno-ekonomi dalam alternatif metode pembuatan telur asin - Roni Kastaman; Faizal Syahmurman (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
Salted eggs are a popular product, but their fragile nature requires preservation methods. One such method is salting. The production process involves direct costs (raw materials and labor) and indirect costs. Minimizing production costs is crucial for maximizing profit and shaping the company's strategy.This study aims to compares the method of curing salted eggs using red bricks and ash with salting eggs using reverse osmosis technology. Reverse osmosis method is an innovative approach in salted egg production that replaces the traditional salting method. In this method, eggs are not soaked in a salt solution but processed using high-pressure equipment to remove water from the eggs and introduce salt into them. This allows for a reduction in the time required for the salted egg production process. The result showed that the Total cost of production per one product cycle with the reverse osmosis method has a lower cost than conventional methods of IDR.257.88. The red brick method has a total cost of IDR.993,401, and the method of ash rub was the highest, with a total cost of IDR.1.017.701.Therefore, the reverse osmosis method becomes the best salting method in a cost-efficient way and has better performance.